Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae) - Polotow, Daniele; Griswold, Charles (Zootaxa, 2018)
The new zoropsid spider genus Chinja Polotow & Griswold is diagnosed and described and the following two new species are described: C. chinja sp. nov. and C. scharffi sp. nov. The species were collected in the Eastern Arc Mountains of Tanzania and appear to be endemic to this region. The genus belongs to the oval-calamistrum clade (OC Clade), which also includes Dionycha and Lycosoidea. Based on the synapomorphies and diagnostic characters of members of the OC Clade, Chinja is considered a member of Zoropsidae, although without a clear subfamily placement due to insufficient data. Males of Chinja can be distinguished from other Zoropsidae by a straight PER, by lacking a tibial crack, by having a male palpal cymbium with a retrobasal process and the male palpal tibia with an RTA and a retromedian cluster of stout setae. Females have a divided cribellum with cribellar spigots evenly arranged, and the epigynum with the median plate broad and laterally procurved into hooks, and the lateral lobes each with a wide tooth. The following set of characters can be also helpful to identify the genus: presence of a third tarsal claw, absence of claw tufts and presence of a cribellum and calamistrum.